Evaluation of iceA1 Gene Expression of Helicobacter pylori Risk Factor of Gastric Cancer in Transgenic Brinjal - Mehran, Mohammad Javad; Sathish Kumar, Basaralu Yadurappa; Haraprasad, Nanjundappa; Barzigar, Rambod; Fakrudin, Bashasab; Paul, Sayan (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: The advancement of plant biotechnology improved crop production by revolutionizing plant science. Humans were commonly infected by Helicobacter pylori, and it was closely linked to stomach ulcers and cancer. In addition to traditional vaccines for H. pylori, transgenic plants have also been produced to produce its antigens as well as edible and non-edible parts that can produce an immune response after consumption. The protein present in H. pylori associated with virulence (iceA1) is believed to predispose to stomach cancer. Objectives: The current study was aimed to evaluate the iceA1 gene expression within brinjal plant to produce novel transgenic lines LC420461-B7, -B10, -B15, -B22 and -B27. Materials and Methods: In the present study, amplified iceA1 gene from H. pylori strain 26695 was transformed into callus of brinjal (from leaf explants) through Agrobacterium tumefacians (EHA105). pBI121 vector was used in constructing the plant expression vector, and the transgenics generated were further evaluated by quantitative Real-Time PCR and western blot analysis. Results: Out of the 46 plants obtained five of them were found to be positive for the iceA1 expression. Both real time and western blot confirmed of the presence of expressed gene iceA1 within the plant sample leaves. By studying transgenic brinjal, the study may result in an H. pylori vaccine candidate. As well, the data can be used by researchers to get valid scientific information.
Keywords: Helicobacter pylori; Transgenic brinjal; iceA1; Agrobacterium; Callus induction; Real-time PCR